Sensitivity of Medicare claims to identify cancer recurrence in elderly colorectal and breast cancer patients - Warren, Joan L. (2016)
BACKGROUND: Researchers are increasingly interested in using observational data to evaluate cancer outcomes following treatment, including cancer recurrence and disease-free survival. Because population-based cancer registries do not collect recurrence data, recurrence is often imputed from health claims, primarily by identifying later cancer treatments after initial treatment. The validity of this approach has not been established. RESEARCH DESIGN: We used the linked SEER- Medicare data to assess the sensitivity of Medicare claims for cancer recurrence in patients very likely to have had a recurrence. We selected newly diagnosed stage II/III colorectal (CRC n=6,910) and female breast cancer (n=3,826) patients during 1994–2003 who received initial cancer surgery, had a treatment break, and then died from cancer in 1994–2008. We reviewed all claims from the treatment break until death for indicators of recurrence. We focused on additional cancer treatment (surgery, chemotherapy, radiation therapy) as the primary indicator, and used multivariate logistic regression analysis to evaluate patient factors associated with additional treatment. We also assessed metastasis diagnoses and end-of-life care as recurrence indicators. RESULTS: Additional treatment was the first indicator of recurrence for 38.8% of CRC patients and 35.2% of breast cancer patients. Patients ages 70 and older were less likely to have additional treatment (p<0.05), in adjusted analyses. Over 20% of patients either had no recurrence indicator before death or had end-of-life care as their first indicator. CONCLUSIONS: Identifying recurrence through additional cancer treatment in Medicare claims will miss a large percentage of patients with recurrences; particularly those who are older.